Eksperimentasi Pembelajaran Matematika dengan Strategi Cooperative Integrated Reading and Composition (CIRC) dan Mind Mapping terhadap Pemahaman Konsep ditinjau dari Kemandirian Belajar Pada Siswa Kelas VIII SMP N 1 Mojolaban Tahun 2014/2015 - Kadarsih, Wulan; , Rita P. Khotimah, S.Si., M.Sc (2015)
This study aims to: (1) Determine the influence strategy Cooperative Integrated Reading and Composition (CIRC) and Mind Mapping to the understanding of mathematical concepts. (2) Determine the influence of students independence learning to the understanding of mathematical concepts. (3) Knowing the interaction effect between learning strategies and independent learning to the understanding of mathematical concepts. Quantitative research with random experimental design types posttest-only control group. The study population consisted of seven class VIII SMP N 1 Mojolaban. Samples were students in two classes, namely class VIIIA and VIIIB. Sampling technique is random sampling by lottery. Data collection techniques with methods of test, questionnaire and documentation. Data were analyzed using analysis of variance two different cell. Based on hypothesis testing, the conclusion is: (1) there is no influence strategy Cooperative Integrated Reading and Composition (CIRC) and Mind Mapping to the understanding of mathematical concept. (2) there are significant levels of independence learning on understanding of mathematical concept. (3) there is no interaction effect between learning strategies and independent learning for understanding of mathematical concept.